Pelatihan Mengidentifikasi Kesulitan Belajar Siswa Anak Yang Berhadapan dengan Hukum Selama Pandemi Covid-19 - Moses Glorino Rumambo Pandin; Christinawati Christinawati (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
This paper will present a research process on learning models for children who faced the law during the pandemic at the Children's Penitentiary. The Covid-19 pandemic is haunting people's lives around the world, including learning activities, especially for children. Teachers, are required to remain present in classes with strict health protocols, so there is no difference before and during a pandemic. The difference demanded is the model and method of learning that must vary so that students can remain focused, not bored, and remember the lessons. Teachers must be able to understand the circumstances and needs of students well. The learning model the author offers is a therapeutic model. The learning model offered in community service activities is a therapeutic model. This activity applies descriptive analysis method. At the beginning, the teacher tried one participant who was selected because of his extreme behavior. Based on the pictures that student made, and what the student wrote, then analyzed the teachers who had been trained using the data on the difficulties experienced by the participants as the basis for forming a teaching model according to the circumstances of the students.